Resistencia a la fractura de dientes tratados endodónticamente rehabilitados con postes de fibra de vidrio vs postes colados - revisión sistemática de la literatura (2021)
Teeth with endodontic treatment and with loss of dental structure are usually restored with fiberglass posts or with cast posts, and are susceptible to failures that can lead to tooth loss because they are not restorable.